Models of data and their processing for introductory courses of computer science (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Evolution of secondary school course on Informatics during 1990s is discussed. This evolution gave for secondary school graduates rather high level knowledge of applications usage. On the other hand Informatics became purely pragmatic matter within generally academic nature of secondary school curricula. As the result graduates of secondary schools are not prepared enough for mastering of university’s course in Computer Science. Authors are not aware of serious studies and methods of prevention of such negative habits caused by evolution of Informatics course. In this article one method applied in university’s introduction course of Computer Science is considered. The method provides use of algorithmic system closed to the human mind, and to some extent compensates topics removed from the Informatics course in secondary school.